APEC and economic liberalization in the Philippines - Tecson, Gwendolyn R. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1995)
The author raises a number of issues related to the Philippines' participation in APEC. First is the issue of whether the country's economic interests are consistent with the objectives of APEC. The author surveys the policy goals and current initiatives towards economic liberalization in the country and notes the "attitudinal shift" among business leaders, both of which appear to be consistent with the APEC vision of creating a free and open trade and investment regime in the Asia-Pacific region. The second issue addressed is whether the country needs APEC. Finally, the author presents some of the expectations as well as apprehensions of a developing country like the Philippines, given the requirements of membership in APEC.